Fish Allergenicity Modulation Using Tailored Enriched Diets—Where Are We? - Schrama, Denise; Czolk, Rebecca; Raposo de Magalhães, Cláudia; Kuehn, Annette; Rodrigues, Pedro M. (Frontiers in Physiology, 2022)
Food allergy is a chronic disease that affects millions of citizens worldwide, with no cure available and with the clinical management relying on a strict avoidance diet. The chronicity, prevalence, and the potential fatality of food allergy make it a serious socio-economic problem. Fish is considered the third most allergenic food in the world, affecting part of the world population with a higher incidence in children and adolescents. The main allergen in fish, responsible for the large majority of fish-allergic reactions in sensitized patients, is a small and stable calcium-binding muscle protein named beta-parvalbumin. Targeting the expression or/and the 3D conformation of this protein by adding specific molecules to fish diets has been the innovative strategy of some researchers in the fields of fish allergies and nutrition. This has shown promising results, namely when the apo-form of β-parvalbumin is induced, leading in the case of gilthead seabream to a 50% reduction of IgE-reactivity in fish allergic patients.